Ruthenium(II)-Tris-pyrazolylmethane Complexes Inhibit Cancer Cell Growth by Disrupting Mitochondrial Calcium Homeostasis - Cervinka, Jakub; Gobbo, Alberto; Biancalana, Lorenzo; Markova, Lenka; Novohradsky, Vojtech; Guelfi, Massimo; Zacchini, Stefano; Kasparkova, Jana; Brabec, Viktor; Marchetti, Fabio (Journal of medicinal chemistry, 2022)
While ruthenium arene complexes have been widely investigated for their medicinal potential, studies on homologous compounds containing a tridentate tris(1-pyrazolyl)methane ligand are almost absent in the literature. Ruthenium(II) complex 1 was obtained by a modified reported procedure; then, the reactions with a series of organic molecules (L) in boiling alcohol afforded novel complexes 2-9 in 77-99% yields. Products 2-9 were fully structurally characterized. They are appreciably soluble in water, where they undergo partial chloride/water exchange. The antiproliferative activity was determined using a panel of human cancer cell lines and a noncancerous one, evidencing promising potency of 1, 7, and 8 and significant selectivity toward cancer cells. The tested compounds effectively accumulate in cancer cells, and mitochondria represent a significant target of biological action. Most notably, data provide convincing evidence that the mechanism of biological action is mediated by the inhibiting of mitochondrial calcium intake.
Keywords: homeostáza; Cell Line, Tumor; Mitochondria; Neoplasms; nádory; lidé; Antineoplastic Agents; Homeostasis; protinádorové látky; komplexní sloučeniny; vápník; mitochondrie; voda; Coordination Complexes; Water; Calcium; Ruthenium; nádorové buněčné linie; ruthenium; Humans